The Difference Between Using MA-11 and EM-4 in Corn Slamper Fermentation to Increase Dry Matter and Organic Matter Digestibility - Prabowo, Risky Jati; Sukaryani, Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study intends to assess the impact of employing two types of bioactivators, namely MA-11 and EM-4, on the digestibility of dry matter (KcBK) and digestibility of organic matter (KcBO) in fermented corncobs. One potential solution to the limited availability of feed is the use of agricultural waste as animal feed, which includes corncob fermentation. The research was carried out using a Completely Randomized Design (CRD) with three treatments and four replications, namely T0 (control), T1 (2% MA-11), and T2 (2% EM-4). The fermentation process was carried out anaerobically for 7 days. The digestibility data were analyzed using ANOVA and continued with the Duncan test. The results showed that treatment T1 (MA-11) produced the highest digestibility value, namely KcBK of 66.37% and KcBO of 67.48%. Treatment T2 (EM-4) showed a KcBK of 64.83% and a KcBO of 64.18%, while the control (T0) had the lowest values, namely KcBK 61.46% and KcBO 61.76%. Although statistically there was no significant difference between treatments (p > 0.05), the increase in biological digestibility was significant. This increase is thought to be caused by the activity of lignocellulolytic and proteolytic microorganisms in MA-11, which are capable of breaking down fibers and complex organic compounds. It can be concluded that corncob fermentation using MA-11 is more effective than EM-4 in improving the nutritional quality and digestibility of feed ingredients. This technology can be an alternative to utilizing agricultural waste as an efficient feed source for ruminant livestock.